MODEL PEMBELAJARAN BERBASIS GAME PADA MATA PELAJARAN FIQIH DI MTS AT-TAUFIQ BOGEM DIWEK JOMBANG - Saputra, Randy Achmadi; Aida Arini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of game-based learning models in the Fiqh subject at MTs At-Taufiq Bogem Diwek Jombang. The research departs from the observation that conventional Fiqh instruction tends to be teacher-centered and heavily theoretical, resulting in suboptimal student engagement and motivation. Game-based learning emerges as an innovative alternative that integrates play elements into academic activities, aiming to foster a more engaging, dynamic, and student-centered learning environment. A qualitative case study approach was employed, with data collected through direct observation, in-depth interviews with the school principal, Fiqh teacher, and students, as well as documentation. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing, with validity ensured through source and method triangulation. Findings indicate that three game models, snakes and ladders, role-playing, and collaborative games, significantly enhanced students' motivation, active participation, collaborative skills, and comprehension of Fiqh material. Supporting factors included high student enthusiasm and the teacher's facilitative role, while inhibiting factors encompassed classroom management complexity, time constraints, and varying student abilities. The study concludes that game-based learning constitutes an effective pedagogical approach for improving Fiqh instruction quality, contingent upon adequate teacher preparedness, appropriate media design, and effective classroom management.